Peningkatan Keterampilan Digital Pemuda Dan Pelaku UMKM Kota Cirebon Melalui Pelatihan Video Editing - Arif Rinaldi Dikananda; Bani Nur Hakim; Aulia Nur Rochmah; Mochamad Arief Saputra (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Video editing training is a strategic solution to the challenge of low digital skills of youth and Micro, Small and Medium Enterprises (MSMEs) in Cirebon City. This program aims to empower the community through capacity building in creating effective and attractive promotional video content. Activities were carried out through a participatory and practice-based approach, including an introduction to editing software, basic visual storytelling techniques, and content optimization for social media. The results of the training showed a significant improvement in participants' skills, with 85% able to produce promotional videos independently. In addition, this training encourages collaboration between creative youth and MSME players, expands the reach of digital marketing, and opens new job opportunities in the creative industry. With the improvement of digital skills, MSME players become more competitive, while youth have alternative income in the digital era. This program contributes to the growth of the creative economy and the reduction of unemployment in Cirebon City.